The impact of a discrepancy between actual and preferred living arrangements on life satisfaction among the elderly in China (Clinics, 2015)
OBJECTIVES:To explore the effects of a discrepancy between actual and preferred living arrangements on the relationship between living arrangements and life satisfaction among the elderly in China.METHODS:Secondary analysis of the 2005 dataset of the Chinese Longitudinal Healthy Longevity Survey was performed. A binary logistic regression model was used to analyze the relationship between life satisfaction and living arrangements.RESULTS:Among those with concordant actual and preferred living arrangements, living in a nursing home increased the likelihood of life satisfaction, whereas living alone and living with a spouse decreased the likelihood of life satisfaction compared to living with the next generation and a spouse. Among those with discordant living arrangements, there were no differences in life satisfaction between the various living arrangements, except that living with a spouse increased life satisfaction compared to living with the next generation and a spouse.CONCLUSIONS:A discrepancy between actual and preferred living arrangements modifies the relationship between life satisfaction and actual living arrangement. Living in a nursing home is a good option for Chinese elder care only if the older individual emotionally accepts it. Living alone or with a spouse is not a good arrangement for elder care, even though it is often preferred by the elderly. Those with discordant living arrangements are more satisfied living with their spouses.